PREPARATION, CHARACTERIZATION AND EVALUATION OF FLOATING MICROPARTICLES OF CIPROFLOXACIN - Durgapal, Sumit; Mukhopadhyay, Sayantan; Goswami, Laxmi (International Journal of Applied Pharmaceutics, 2016)
Objective: The main purpose of this study is to prepare a floating micro articulated drug delivery system of ciprofloxacin by using non-aqueous solvent evaporation technique to increase the bioavailability and therapeutic effectiveness of the drug by prolonging its gastric residence time. Methods: Floating microparticles were prepared by using different low-density polymers such as ethyl cellulose and hydroxypropyl methylcellulose either alone or in combination with the aid of non-aqueous solvent evaporation technique. All the formulated microparticles were subjected to various evaluation parameters such as percentage yield, drug content, drug entrapment, rheological studies, floating characteristics and in vitro drug release studies. Results: Drug-excipient compatibility studies performed with the help of FTIR instrument indicated that there were no interactions. Results revealed that non-aqueous solvent evaporation technique is a suitable technique for the preparation of floating microspheres as most of the formulations were discrete and spherical in shape with a good yield of 65% to 85% and 15 to 22 h of floating duration with 90% of maximum percentage floating capacity shown by formulation FM9. Though, different drug-polymer ratios, as well as a combination of polymers, play a significant role in the variation of overall characteristics of formulations. Based on the data of various evaluation parameters such as particle size analysis, drug content, drug entrapment, rheological studies and in vitro drug release characteristics formulation FM9 was found to fulfil the criteria of ideal floating drug delivery system. Conclusion: Floating microparticles were successfully prepared, and from this study, it can be concluded that the developed floating microspheres of ciprofloxacin can be used for prolonged drug release in the stomach to improve the bioavailability and patient compliance.